The Role of Islamic Religious Education in Overcoming Negative Behavior of Generation Z on Social Media - Faizudin; Wasehudin (TADRIS: Jurnal Pendidikan Islam, 2026)
The rapid advancement of social media platforms has greatly influenced Generation Z’s behavioral patterns, especially regarding ethical considerations and digital accountability. Islamic Education (PAI) has the potential to serve as a mechanic to foster ethical behavior in the digital realm; however, teachers continue to face challenges in aligning religious principles with contemporary digital practices. This study was designed to investigate the function of Islamic education in fostering ethical behavior among students in the context of social media. The research methodology employed is qualitative, using a case study approach at SMK IT Al-Khairiyah Cilegon, incorporating the perspectives of both PAI teachers and students as participants. The findings show that the incorporation of Islamic values in religious education significantly enhances students’ understanding of the critical nature of digital ethics, despite the constraints posed by curriculum limitations and technological challenges. The study advocates the integration of digital ethics into the PAI curriculum and emphasizes the need for enhanced training for teachers to effectively utilize technology in instructional practices. The implications of this study underscore the need for curriculum modernization and the imperative to enhance teachers’ ability to nurture students’ ethical and responsible digital identities.